2009
DOI: 10.1002/ejoc.200801266
|View full text |Cite
|
Sign up to set email alerts
|

Click Chemistry Inspired Synthesis of Novel Ferrocenyl‐Substituted Amino Acids or Peptides

Abstract: This work reports on the synthesis of a wide range of ferrocenyl-substituted amino acids and peptides in excellent yield. Conjugation is established via copper-catalyzed 1,3-dipolar cycloaddition. Two complementary strategies were employed for conjugation, one involving cycloaddition of amino acid derived azides with ethynyl ferrocene 1 and the other involves cycloaddition between amino acid derived alkynes with ferrocene-derived azides 2 and 3. Labeling of amino acids at multiple sites with ferrocene is discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…[1] In this respect, nucleobases remain attractive targets for ferrocenyl conjugation. Pyrimidines and purines substituted by a ferrocenyl moiety present interesting organometallic conjugates because their structures incorporate both biologically and electrochemically active components.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In this respect, nucleobases remain attractive targets for ferrocenyl conjugation. Pyrimidines and purines substituted by a ferrocenyl moiety present interesting organometallic conjugates because their structures incorporate both biologically and electrochemically active components.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Recently, we developed an efficient methodology to conjugate ferrocene by using click chemistry at both the N and C terminus of a peptide with azidomethylferrocene (1) and 1-ethynylferrocene (3) as starting materials. [12] Incorporating azido functionality at the N terminus was achieved through the chloroacetyl derivative of the respective amino acid followed by displacement of chloride with NaN 3 in DMF. Thus, the azidoacetylated amino acids were clicked under CuAAC conditions with 1-ethynylferrocene (3) to furnish the desired conjugates 20-24 in excellent yield (Scheme 4).…”
Section: Introductionmentioning
confidence: 99%
“…The same kind of dendritic architecture 32 has been constructed starting from lysine under similar conditions. [12] The electrochemical studies of the dendrimer-like compounds revealed that all the ferrocenyl groups at the periphery are in an electrochemically equivalent environment. The CV for 31 showed only one redox peak, thereby suggesting prevalence of electrochemical equivalence of the ferrocene groups (Figure 1) Later, we developed the synthesis of various chiral entities such as modified amino acids, chiral alcohols, diols, esters, and amines that carry azido groups, which were clicked with 1-ethynylferrocene (3) with a view toward studying their utility in asymmetric catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Copper-catalyzed azide acetylene coupling (Cu-ACC) reactions of ferrocenylmethyl azides has been reported, 17 including the “labelling” of estradiol with a redox active organometallic functionality. 17a-c In addition, estradiol complexes of metal carbonyls have been previously prepared for Cr, Mo, W, Mn, Re, Ru, and Co as both tracers for the steroid in biological systems by FT IR, and as radiopharmaceuticals (Tc).…”
Section: Results and Discussion8mentioning
confidence: 99%
“…17a-c In addition, estradiol complexes of metal carbonyls have been previously prepared for Cr, Mo, W, Mn, Re, Ru, and Co as both tracers for the steroid in biological systems by FT IR, and as radiopharmaceuticals (Tc). 18 While there have been a number of (5-azido-1,3-cyclodiene)iron complexes reported, 19 to our knowledge there are no reports of Cu-ACC reactions from these azides.…”
Section: Results and Discussion8mentioning
confidence: 99%